The Efficacy of Dextran-40 as a Venous Thromboembolism Prophylaxis Strategy in Cytoreductive Surgery and Hyperthermic Intraperitoneal Chemotherapy. Issue 2 (February 2017) - Foster, Jason M.; Sleightholm, Richard; Watley, Duncan; Wahlmeier, Steven; Patel, Asish
The incidence of venous thromboembolism (VTE) in peritoneal malignancies can approach 30 to 50 per cent without prophylaxis. Prophylaxis in cytoreductive surgeries (CRS) presents a challenge to preoperative heparin-based therapy because of an increased risk of coagulopathy and potential for bleeding. Herein, we report the large series of CRS and hyperthermic intraperitoneal chemotherapy receiving dextran-40 prophylaxis. Retrospective chart review of peritoneal malignancies patients undergoing CRS at University of Nebraska Medical Center identified 69 individuals who received dextran-40 between 2010 and 2013. The incidences of VTEs, perioperative bleeding, complications, morbidity, and mortality were determined in-hospital and at 90 days. Of the 69 patients treated, the 30-day VTE rate was 8.7 per cent, and no pulmonary embolisms, bleeding, anaphylactoid reaction, or mortality were observed with dextran usage. The specific VTE events included three upper extremity and three lower extremity VTEs. No additional VTE events were identified between 30 and 90 days. In conclusion, dextran-40 prophylaxis was not associated with any perioperative bleeding events, and the observed incidence of VTE was comparable to reported heparin-based prophylaxis in CRS/hyperthermic intraperitoneal chemotherapy patients. This data supports further exploration of dextran-40 as a VTE prophylactic agent in complex surgical oncology cases.